Morbidity and factors associated with frailty in post-COVID-19 elderly patients attended at a reference center - Ely Carlos Pereira de Jesus; Victor Guilherme Pereira; Zilá Aparecida Soares Pereira; Maria Suzana Marques; Cristiane Vieira da Silva; Leila das Graças Siqueira; Luciana Colares Maia; Antônio Prates Caldeira (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To assess the morbidity profile and identify factors associated with frailty syndrome in post-COVID-19 elderly patients treated at the only Reference Center for Elderly Health Care in northern Minas Gerais. Methods: This is a case series study, utilizing the Clinical-Functional Vulnerability Index-20 (CFVI-20) and Comprehensive Geriatric Assessment (CGA) to characterize and evaluate the health condition of the group. To define the variables associated with frailty, a multivariate analysis was conducted. Results: The study included 204 elderly individuals, with a predominance of females (63.7%). The variables associated with frailty were cognitive impairment (OR: 2.95; 95% CI: 1.12-7.80; p=0.029), the presence of five or more comorbidities (OR: 11.55; 95% CI: 2.22-60.01; p=0.004), and impairment in instrumental activities of daily living (OR: 41.97; 95% CI: 5.47-321.93; p<0.001). Conclusions: The results of this study highlight the need for a well-established and prepared coordination of integrated care to meet the demands of the post-COVID-19 elderly population.